Implementation strategy of multimodal literacy text as a means to optimize literacy in Indonesian language lessons for elementary school students - Saputra , Dimas Teguh; Etika Rahmawati, Laili; Markhamah, Markhamah (Universitas Ahmad Dahlan, 2025)
Multimodal literacy texts in Indonesian language learning in primary schools are needed to improve students' literacy skills holistically, along with the demands of the digital era that require students to understand various forms of visual, audio and digital-based texts. Literacy is an important skill in the industrial revolution 4.0 era, but literacy skills in Indonesia are still relatively low, especially in reading and numeracy literacy. The school implemented a multimodal literacy strategy that includes integrating text with visual and audio media, implementing collaborative learning, writing activities and utilising technology. The purpose of this study is to describe the implementation strategy of multimodal literacy texts in improving Indonesian literacy skills at Bulukantil State Elementary School, Surakarta. This study used a qualitative approach method, data collection techniques through interviews, observation, and documentation. The results showed that the integration of visual and audio media can increase students‘engagement in understanding the text; collaborative learning develops students’ social skills and digital literacy; and writing activities help students strengthen memory and communication skills. The utilization of technology allows access to more diverse learning resources, making learning more interactive and engaging. Overall, the results of this study can be concluded that the implementation of multimodal literacy texts is effective in improving students' Indonesian literacy skills, preparing them for the computer-Based National Assessment, as well as building positive character, creativity, activeness and independence.